A Systematic Review of Organizational Response to the COVID-19 in the Hospitality Industry - Nidhi Nidhi; Rajib Lochan Dhar (ASEAN Journal on Hospitality and Tourism, 2022)
Pandemic COVID-19 has placed an unforeseen and unparalleled challenge to organizations worldwide. In an attempt to mitigate its consequences, the organizations have resorted to specific measures and adopted new mechanisms for their survival. This research encompasses a review of available literature on the “organizational responses to the COVID-19” focusing hospitality sector. It also assesses the impact of responsive measures on hospitality employees. Lastly, it addresses the new agendas for future research. Through a detailed assessment of data collected from 50 articles, the study explores the structural and functional changes introduced by the organizations to combat the challenges posed by outbreak of Pandemic COVID-19 and reviews the association between workplace response, including employees in the hospitality sector.